SHOCK-INDUCED VAPORIZATION OF ANHYDRITE AND GLOBAL COOLING FROM THE K/T IMPACT - Gupta S.C.; Ahrens T.J.; Yang W. (My University, 2001)
Discovery of abundant anhydrite (CaSO4) and gypsum (CaSO4·2H2O) in the otherwise carbonate sediment comprising the upper 3 km thick layer of the target rock at the K/T impact site has prompted research on these minerals. Evaluation of the severity of the proposed extinction mechanism involving injection of impact-generated SO2 and SO3 into the stratosphere entails determination of criteria for shock-induced vaporization of these minerals. In the present work we present new data on the vaporization criteria of anhydrite. These are based on the reanalysis of the shock wave experiments of Yang and Ahrens [Earth Planet. Sci. Lett. 156 (1998) 125–140], conducted on material with 30% porosity, in which the shock- (fully or partially) vaporized sample interacts with an overlying LiF window. The velocity histories, monitored using a velocity interferometer, are compared with numerical simulations employing an improved equation of state for porous anhydrite and its vaporization products. We also employ the ‘entropy criterion’ for vaporization of material under shock compression. The values of the entropies of incipient and complete vaporization for anhydrite are determined to be 1.65±0.12 and 3.17±0.12 kJ (kg K)−1, respectively, and the corresponding pressures for incipient and the complete vaporization along the Hugoniot for the solid material are 32.5±2.5 and 122±13 GPa, respectively as compared with 81±7 and 155±13 GPa previously reported by Yang and Ahrens. Along with these criteria, the use of the recent estimate of diameter (100 km) for the Chicxulub transient crater [O’Keefe and Ahrens, J. Geophys. Res. 104 (E11) (1999) 27091–27104; Morgan et al., Nature 390 (1997) 472–476] that is smaller than previously assumed, along with Ivanov et al.’s [Geol. Soc. Am. Spec. Pap. 307 (1996) 125–142] 2-D hydrodynamic simulation to determine the shock attenuation and Pope et al.’s [J. Geophys. Res., 102 (E9) (1997) 21645–21664] radiative transfer model, yields the maximum decrease in the average global surface temperature of 12–19 K for 9.0–9.5 years at the K/T boundary. Thus, the global cooling is inferred to have been less severe than that indicated by the upper limit of the range of 5–31 K decrease lasting for ∼12 years calculated by Pope et al. Because ambient global surface temperatures at K/T time were ∼18–20°C warmer than present values, this cooling event produced cold, but not freezing conditions at the Earth’s surface.